Innovative Approaches to Mathematics Instruction Through Historical Perspectives: A Descriptive Systematic Review - Chen, Yijing; Shahrill, Masitah; Abdullah, Nor Azura (Universitas Muhammadiyah Surakarta, 2026)
The integration of the history of mathematics (HOM) into mathematics instruction has gained increasing scholarly attention as educators seek approaches that deepen conceptual understanding, foster epistemological awareness, and situate mathematics within broader cultural and historical contexts. Despite this growing interest, findings regarding its pedagogical value, instructional design principles, and implementation challenges remain dispersed across diverse empirical studies. This study presents a descriptive systematic review of research published between 2000 and 2025 examining the integration of historical perspectives in mathematics education. Following PRISMA-style procedures, 18 empirical studies were identified through a multi-stage screening process based on predefined Thematic synthesis revealed that HOM integration contributes to cognitive–conceptual development, sociocultural identity formation, engagement and affective dimensions, and interdisciplinary connections, including evidence that historically structured tasks can support students’ understanding of foundational mathematical concepts by situating them within meaningful problem contexts. However, these benefits are mediated by instructional design coherence and are constrained by factors such as teacher preparation, curriculum pressures, and assessment alignment. The review suggests that HOM functions not merely as enrichment content but as a pedagogical lens capable of reshaping how mathematical knowledge and learning are conceptualised. Effective implementation therefore requires principled instructional design and systemic support across curriculum, teacher education, and assessment structures.